Bleach. 70 - Kubo, Tite (VIZ Media, LLC, 2017)
As the war between the Soul Reapers and Quincies rages on, childhood friends Jugo and Bazz find themselves on opposite sides of the conflict, while Kenpachi and Mayuri face off against a weird Quincy.